Hubungan sense of humor dengan penyesuaian diri pada Mahasiswa baru dari luar Jawa - Muhammad Nurus Shobah; Agustin Rahmawati; Ritna Sandri (Jurnal Psikologi Tabularasa, 2021)
New students often have difficulty adjusting to their new environment. Moreover, there are very significant cultural and language differences. Difficulty adjusting also has physical impacts, such as stress and depression. Meanwhile, her psychological outlook is like being unable to achieve mental happiness. So in this case it is necessary to develop a sense of humor in making adjustments. This study aims to determine the relationship between a sense of humor and self-adjustment in new students from outside Java. The sample of this research is 99 new students of Merdeka University Malang. The sampling technique uses Random Sampling. The data analysis in this study used the Pearson product moment correlation coefficient technique. The research methods used were the item validity test of the self-adjustment scale and the item validity test for the sense of humor scale and the reliability test using the SPSS 22 computer, namely the cronbach technique for each scale. The results showed that there was a significant relationship with rxy = 0.414 and with p = 0.000, which means that there is a positive relationship between sense of humor and self-adjustment in new students from outside Java.